Respuesta :
Answer:
Add 24 and 40
Step-by-step explanation:
3(8 - 2x) + 40 = 34 use the distributive property a(b + c) = ab+ ac
3(8) + 3(-2x) + 40 = 34
24 - 6x + 40 = 34 combine like terms
-6x + (24 + 40) = 34 Answer: Add 24 and 40
-6x + 64 = 34 subtract 64 from both sides
-6x = -30 divide both sides by (-6)
x = 5
Answer:
Add 24 and 40.
Step-by-step explanation:
Steven is solving the equation [tex]3(8-2x)+40=34[/tex]
Step 1:
[tex]3(8)+3(-2x)+40=34[/tex]
Step 2:
[tex]24-6x+40=34[/tex]
So, according to pemdas, the next step is Add 24 and 40.
Then this becomes:
Step 3:
[tex]64-6x=34[/tex]
So, the answer will be option 2: Add 24 and 40.